2019
DOI: 10.1016/j.healthplace.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

‘If I pay rent, I’m gonna smoke’: Insights on the social contract of smokefree housing policy in affordable housing settings

Abstract: Smoke-free housing policy in multi-unit housing has emerged as a promising tobacco control initiative, yet full compliance remains elusive and is a critical impediment to policy effectiveness. There is a gap in existing research on potential factors preventing optimal smoke-free policy adoption and corresponding solutions. Using qualitative and quantitative data from resident surveys (N=115) as well as key informant interviews, a focus group, and observational fieldwork, this study 1) assesses smoking behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…In general, study results are consistent with evaluations of tobacco policies in public or multi-person housing prior to the nationwide HUD rule. Specifically: a) residents have good knowledge, and are supportive, of the policy, especially non-smokers ( Kennedy et al, 2015 , Rokicki et al, 2016 ); b) residents are concerned that there isn’t enough enforcement ( Hernandez et al, 2019 , Jiang et al, 2018 , Kennedy et al, 2015 ); c) tobacco policies reduce, but do not eliminate self-reported smoking exposure in the building ( Hernandez et al, 2019 , Pizacani et al, 2012 , Rokicki et al, 2016 ); and d) the policy motivates smokers to make positive changes in their tobacco use ( Rokicki et al, 2016 ). Regarding quitting, Pizacani et al (2012) reported a higher policy associated quit rate (14.6%) than in this study (6.4%).…”
Section: Discussionsupporting
(Expert classified)
See 3 more Smart Citations
“…In general, study results are consistent with evaluations of tobacco policies in public or multi-person housing prior to the nationwide HUD rule. Specifically: a) residents have good knowledge, and are supportive, of the policy, especially non-smokers ( Kennedy et al, 2015 , Rokicki et al, 2016 ); b) residents are concerned that there isn’t enough enforcement ( Hernandez et al, 2019 , Jiang et al, 2018 , Kennedy et al, 2015 ); c) tobacco policies reduce, but do not eliminate self-reported smoking exposure in the building ( Hernandez et al, 2019 , Pizacani et al, 2012 , Rokicki et al, 2016 ); and d) the policy motivates smokers to make positive changes in their tobacco use ( Rokicki et al, 2016 ). Regarding quitting, Pizacani et al (2012) reported a higher policy associated quit rate (14.6%) than in this study (6.4%).…”
Section: Discussionsupporting
(Expert classified)
“…Generally, residents were knowledgeable of the smoke-free policy and supportive of it ( Kennedy et al, 2015 , Rokicki et al, 2016 ), with non-smokers more supportive than smokers ( Kennedy et al, 2015 ). However, enforcement of the policy was a concern, with some evidence that such enforcement was poor ( Hernandez et al, 2019 , Jiang et al, 2018 , Kennedy et al, 2015 ). Consistent with these concerns, evaluations of these smoke-free housing policies documented reductions, but not elimination, of smoking within the buildings ( Hernandez et al, 2019 , Pizacani et al, 2012 , Rokicki et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…35,36 These include a sentiment among many residents that they have a right to privacy and autonomy in their homes (counterbalancing overall support for the policy), a lack of tobacco cessation treatment support, and frustration that other building violations, such as marijuana use, are not being addressed. A study by Hernández and colleagues 35 Downloaded From: https://jamanetwork.com/ on 11/24/2020 agenda into a wider healthy-homes policy agenda. Continued evaluation of the implementation process and assessment of consequences for health outcomes is critical to optimize both.…”
Section: Discussionmentioning
confidence: 99%